Optimal large linear complexity frequency hopping patterns derived from polynomial residue class rings - Udaya, Paramapalli; Siddiqi, Mohammad Umar (Institute of Electrical and Electronics Engineers Inc., 1998)
We construct new sequences over finite rings having optimal Hamming correlation properties. These sequences are useful in frequency hopping multiple-access (FHMA) spreadspectrum communication systems. Our constructions can be classified into linear and nonlinear categories, both giving optimal Hamming correlations according to Lempel-Greenberger bound. The nonlinear sequences have large linear complexity and can be seen as a generalized version of GMW sequences over fields